Anti-HERV-K Drugs and Vaccines, Possible Therapies against Tumors - Sepideh Hosseiniporgham; Leonardo Antonio Sechi (Vaccines, 2023)
The footprint of human endogenous retroviruses (HERV), specifically HERV-K, has been found in malignancies, such as melanoma, teratocarcinoma, osteosarcoma, breast cancer, lymphoma, and ovary and prostate cancers. HERV-K is characterized as the most biologically active HERV due to possession of open reading frames (ORF) for all Gag, Pol, and Env genes, which enables it to be more infective and obstructive towards specific cell lines and other exogenous viruses, respectively. Some factors might contribute to carcinogenicity and at least one of them has been recognized in various tumors, including overexpression/methylation of long interspersed nuclear element 1 (LINE-1), HERV-K Gag, and Env genes themselves plus their transcripts and protein products, and HERV-K reverse transcriptase (RT). Therapies effective for HERV-K-associated tumors mostly target invasive autoimmune responses or growth of tumors through suppression of HERV-K Gag or Env protein and RT. To design new therapeutic options, more studies are needed to better understand whether HERV-K and its products (Gag/Env transcripts and HERV-K proteins/RT) are the initiators of tumor formation or just the disorder’s developers. Accordingly, this review aims to present evidence that highlights the association between HERV-K and tumorigenicity and introduces some of the available or potential therapies against HERV-K-induced tumors.